Epidemiological observations on Peste-des-petits ruminants in north India - Kumar, G S; Rathore, B S; Mehrotra, M L (The Indian Journal of Animal Sciences, 2012)
An outbreak of Peste-des-petits ruminants (PPR) occurred during February-May 1994 in sheep and goat population maintained at the IVRI, Izatnagar. The outbreak occurred following introduction of newly purchased sheep and goats for experimental purposes by various divisions of the institute. The morbidity, mortality and case fatality rates in sheep, respectively, were 52.9, 29.3% and 55.4% while these rates in goats were relatively higher i.e., 84.3%, 60.3% and 71.6% respectively. The outbreak subsided after 3 months following antibiotic and supportive therapy of ailing animals and vaccination of healthy animals. Possible source (s) of infection and spread from southern to northern states is discussed.